2021
DOI: 10.1111/hsc.13407
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of people with mild intellectual disability and their family members about family‐based social capital in the Netherlands

Abstract: Families play an important role in the lives of people with intellectual disability as they do for everyone. However, little research has addressed the views of people with intellectual disability about their families by using self‐report. Individual family members may hold different views about their family relationships. Therefore, we used a social capital theoretical perspective to examine (a) how perceptions of people with mild intellectual disability (MID) about their family support networks compare to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Previous research has shown the utility of social capital as a theoretical framework to examine support in the family relationships of people with mild intellectual disabilities (Giesbers et al, 2019(Giesbers et al, , 2020a(Giesbers et al, , 2020b(Giesbers et al, , 2022Kramer et al, 2013;Widmer et al, 2008Widmer et al, , 2013. As families are social network structures in which support is typically provided, families are considered a significant source of social capital (Furstenberg & Kaplan, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has shown the utility of social capital as a theoretical framework to examine support in the family relationships of people with mild intellectual disabilities (Giesbers et al, 2019(Giesbers et al, , 2020a(Giesbers et al, , 2020b(Giesbers et al, , 2022Kramer et al, 2013;Widmer et al, 2008Widmer et al, , 2013. As families are social network structures in which support is typically provided, families are considered a significant source of social capital (Furstenberg & Kaplan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many people with mild intellectual disabilities might not experience bridging social capital at all (Giesbers et al, 2022). Decreased levels of bridging social capital may hinder the autonomy that people with mild intellectual disabilities experience within their families (Woolcock, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations